2017
DOI: 10.1002/cncr.31064
|View full text |Cite
|
Sign up to set email alerts
|

Massage therapy decreases cancer‐related fatigue: Results from a randomized early phase trial

Abstract: SMT produced clinically significant relief of CRF. This finding suggests that 6 weeks of a safe, widely accepted manual intervention causes a significant reduction in fatigue, a debilitating sequela for cancer survivors. Cancer 2018;124:546-54. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 57 publications
0
60
0
3
Order By: Relevance
“…Fatigue-a subjective sense of tiredness, weakness, exhaustion and enervation-is another common side effect that persistently affects patients with breast cancer (Hofman, Ryan, Figueroa-Moseley, Jean-Pierre, & Morrow, 2007;Kinkead et al, 2018). The National…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue-a subjective sense of tiredness, weakness, exhaustion and enervation-is another common side effect that persistently affects patients with breast cancer (Hofman, Ryan, Figueroa-Moseley, Jean-Pierre, & Morrow, 2007;Kinkead et al, 2018). The National…”
Section: Background and Objectivesmentioning
confidence: 99%
“…A systemic review demonstrated that breast pain and weakness in the arms are the most common physical side effects of surgical treatment for breast cancer; these side effects can affect working performance in breast cancer survivors (Zomkowski et al, ). Fatigue—a subjective sense of tiredness, weakness, exhaustion and enervation—is another common side effect that persistently affects patients with breast cancer (Hofman, Ryan, Figueroa‐Moseley, Jean‐Pierre, & Morrow, ; Kinkead et al, ). The National Comprehensive Cancer Network defines cancer‐related fatigue as persistent fatigue associated with cancer and as a side effect of cancer treatment (Berger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…51 As with any physical activity, however, sprains and strains are possible, especially to the knee, and this should be taken into account when recommending this therapy. 52 Effectiveness Not Established-Many treatments, detailed in Figure 4, have insufficient evidence to recommend them for clinical practice in posttreatment cancer survivors (Effectiveness Not Established) including the herbal supplements PG2 (Astragalus membranaceus) 53 and American ginseng, 15,27 and acupuncture, 54,55 biofield energy, 56 massage therapy, 57 laser moxibustion, 44 progressive muscle relaxation (PMR), 35 reflexology, 39 mindfulness-based stress reduction (MBSR), 58 and a multimodal mind-body medicine, nutrition, and exercise treatment. 59…”
Section: Overview Of Interventions For Crf Posttreatmentmentioning
confidence: 99%
“…Qigong, Tai Chi, acupuncture, and Tuina have the function of regulating visceral function, reinforcing Qi and activating blood, and restoring the balance of Yin and Yang. In addition, numerous clinical reports from various sources have shown that Qigong, [ 22 ] Tai Chi, [ 23 ] acupuncture, [ 24 ] and Tuina [ 25 ] are effective for CRF. They can also alleviate depression, [ 26 ] sleep disturbance, [ 27 ] and pain.…”
Section: Introductionmentioning
confidence: 99%